Protective effects of silymarin in broiler feed contaminated by mycotoxins: growth performance, meat antioxidant status, and fatty acid profiles - Armanini E.H. (2021)
© 2021, The Author(s), under exclusive licence to Springer Nature B.V.The aim of this study was to determine whether the inclusion of silymarin in broiler feed was able to mitigate the adverse effects of mycotoxin on growth performance, health status, liver oxidative stress, and meat fatty acid profiles. A completely randomized design with four treatments, four repetitions, and 15 chicks per repetition was used, with the following groups: (a) feed without additives (NoMyc-NoSil), (b) feed supplemented with silymarin (NoMyc-Sil), (c) feed contaminated with mycotoxin (Myc-NoSil), and (d) feed contaminated with mycotoxin and supplemented with silymarin (Myc-Sil). Growth performance, intestinal and liver health, and meat quality were assessed. The consumption of feed contaminated with mycotoxin delayed weight gain and increased the feed conversion ratio; however, the addition of silymarin prevented these adverse effects on the chicken industry. Serum ALT activity was higher in Myc-NoSil broilers than in other groups. Intake of silymarin in healthy birds increased serum globulin concentration and reduced albumin concentration and ALT and AST serum activities compared to the Myc-NoSil group. The NoMyc-Sil birds had greater villus heights and crypt depths. Luminosity and water loss by cooking were affected by mycotoxin ingestion, changes that did not occur in the meat of birds that were supplemented with silymarin. The sum of saturated and monounsaturated fatty acids in the meat did not change among treatments, unlike the sum of polyunsaturated fatty acids higher in the meat of birds that consumed silymarin. We conclude that silymarin is a potential additive in broiler feed; it reduces impairment of growth performance at the end of the productive cycle, prevents oxidative stress, improves meat quality, and increases polyunsaturated fatty acids.